The Impact of Logical Fallacies in Business Communication: Exploring their Impact on Decision Making and Interpersonal Relationships in the Professional World - Lorence Manalu; Fernando Manalu; Dermawan Manalu; Ningsih Manalu; Masduki Asbari; Nia Mintari; Elsy. C. M Pasaribu (International Journal of Management and Economic Research (IJOMER), 2025)
Effective business communication is critical in improving organizational efficiency, speeding up decision-making, and reducing conflict. However, in practice, communication is often hampered by logical fallacies, which can undermine the quality of the message conveyed and interfere with rational decision-making. This research aims to analyze the impact of logical fallacies in business communication, focusing on their influence on organizational decision-making and interpersonal relationships in the professional world. This research uses a qualitative descriptive approach, analyzing the different types of logical fallacies that appear in business communication as well as their influence on organizational dynamics. The results show that fallacies such as ad hominem, false dilemma, slippery slope and overgeneralization often lead to irrational, limited or biased decisions which in turn are detrimental to the organization. In addition, the use of fallacies can worsen interpersonal relationships, triggering conflict, tension and distrust among individuals in a team, which hinders constructive cooperation. The conclusion of this study is that logical fallacies have a significant impact on both aspects, and to create more effective communication and rational decision-making, it is imperative for organizations to avoid the use of fallacies. Critical thinking training that focuses on the detection and avoidance of fallacies is an important step to improve the quality of communication and the effectiveness of decisions made in organizations.